Gangguan Psikotik Pasca Trauma Kepala: Case Report - Sihombing, Linda Agustina; Prasetya, Era Catur (Green Publisher Indonesia, 2025)
Severe head trauma due to a traffic accident can trigger psychiatric disorders with varying post-injury onsets. Organic mental disorders can appear as secondary neuropsychiatric manifestations due to structural or functional damage to the brain, such as head trauma. This case describes patients without a history of underlying psychiatric and organic symptoms, as well as without a history of substance abuse. The patient experiences post-head trauma psychotic disorders. Patients in the case receive multidisciplinary treatment, from the psychiatric side in the form of atypical antipsychotic therapy and acetylcholinesterase inhibitors as well as social and family support. Psychotic symptoms that arise after trauma need to be recognized, treated, both pharmacologically and non-pharmacologically to help improve the patient's quality of life after trauma.